2006
DOI: 10.1093/aje/kwk040
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Risk Factors for Cutaneous Melanoma in Women: A Case-Control Study

Abstract: Reproductive hormonal factors may have a potential role in cutaneous melanoma. This study estimated the risk of melanoma in women related to self-reported changes in nevi during pregnancy, while using oral contraceptives and/or hormone replacement therapy. Trained interviewers administered a questionnaire obtaining information about oral contraceptive use, hormone replacement therapy, reproductive history, sun exposure, occupation, and medical history from 318 Caucasian women newly diagnosed between 1991 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 31 publications
4
48
0
6
Order By: Relevance
“…Moreover, only a few studies have examined associations according to histologic subtype 14,15,25 or menopausal status, 7,8 which may be important given the possible link between reproductive and hormonal factors and risk of melanoma in women. 6,14,[26][27][28][29][30][31] The prevalence of overweight and obesity is growing dramatically in most parts of the world, and generally is higher in women than in men. 32 This is predicted to have major consequences on the incidence of obesity-related diseases.…”
mentioning
confidence: 99%
“…Moreover, only a few studies have examined associations according to histologic subtype 14,15,25 or menopausal status, 7,8 which may be important given the possible link between reproductive and hormonal factors and risk of melanoma in women. 6,14,[26][27][28][29][30][31] The prevalence of overweight and obesity is growing dramatically in most parts of the world, and generally is higher in women than in men. 32 This is predicted to have major consequences on the incidence of obesity-related diseases.…”
mentioning
confidence: 99%
“…In a Swedish registry-based study of the risk of cutaneous malignant melanoma in mothers, similar results for the effects of age at first birth and parity (family size) were reported (15). However, one recent case-control study reported increasing risk of cutaneous malignant melanoma in mothers by parity (30).…”
Section: Prenatal Markers and Cutaneous Malignant Melanoma Risk Cancementioning
confidence: 67%
“…Moreover, a large French study of 460 women with melanoma, as compared with controls in a Cox proportional hazard analysis, suggested a modest reduction in the relative risk for melanoma associated with parity ≥3 pregnancies [ 154 ]. In contrast, the melanoma case-control study of Lea et al [ 148 ] reported an increased risk of melanoma in women less than 55 years of age associated with live birth 5 years before diagnosis (OR = 2.6) and with the history of ≥3 births (OR = 3.3, p for trend <0.001) [ 148 ]. Suffi ce it to say that the data remain confl icting but that the preponderance of the evidence does not indicate an increased risk of melanoma, or worsened prognosis from melanoma, associated with pregnancy or parity.…”
Section: Pregnancy Statusmentioning
confidence: 96%
“…A retrospective, population-based study of 412 melanomas diagnosed during or within 1 year after pregnancy and agematched, nonpregnant women from a California registry uncovered no differences in disease stage at presentation of melanoma or in melanomarelated survival by multivariate and Kaplan-Meier product limit analyses [ 147 ]. A review of the subject published in 2009 asserted that prognosis for localized primary melanoma does not appear to be adversely affected by pregnancy [ 152 ], nor is there evidence that hormone replacement therapy increases a woman's risk of melanoma [ 148 ].…”
Section: Pregnancy Statusmentioning
confidence: 99%